Answer:
∠PQS= 3(x +5)
Step-by-step explanation:
∠PQR = 5x + 25
∠SQR+∠PQS= 5x+25
∠PQS = ∠PQR-∠SQR
∠PQS= (5x + 25 )-(2x + 10)
∠PQS = 5x+25 -2x-10
∠PQS= 3x +15
∠PQS= 3(x +5)
Answer:
Step-by-step explanation:
By triangle sum theorem,
Sum of all angles of a triangle is 180°.
m∠1 + m∠2 + m∠3 = 180°
(m∠1 + m∠3) + m∠2 = 180°
2(m∠1) + 70° = 180° {Given → m∠1 = m∠3]
2(m∠1) = 110°
m∠1 = 55°
Therefore, m∠1 = m∠3 = 55°
Answer:
f(x)=6x³ - 8x
Step-by-step explanation:
Distribute
4x+3x-6=-20
7x-6=-20
add 6 to both sides
7x=-14
divide both sides by 7
x=-2